Using video to assess preschool teachers’ pedagogical knowledge: explicit and higher-order knowledge predicts quality - Mathers, SJ (Elsevier, 2020)
Theory suggests that effective real-time decision-making in classrooms requires teachers to have flexible access to rich and well-organised knowledge of effective teaching practices. Yet prior research on the role and importance of procedural knowledge has been equivocal. This exploratory study used a new video measure of procedural knowledge to examine relationships with observed classroom quality, and establish which opportunities to learn (qualifications, professional development, classroom experience) predict greater knowledge. It focused on preschool teachers’ knowledge of oral language pedagogy, on the basis that early language provides the foundation for children’s later learning.   The sample comprised 104 teachers participating in a wider RCT, designed to evaluate a professional development intervention. Teachers were shown two short videos of classroom interactions and asked to identify instances of effective practice. Responses were coded to capture three facets: perceiving (the ability to identify salient language-supporting strategies); naming (the use of specific professional vocabulary to describe interactions); and interpreting (the ability to interpret the interactions observed). The three facets could be empirically distinguished. Explicit and higher-order procedural knowledge (naming, interpreting) most strongly predicted classroom quality. Formal learning opportunities were stronger predictors of procedural knowledge than classroom experience. Intervention effects on classroom quality were mediated by knowledge. Implications for workforce development are discussed.